Stress and anxiety management intervention to enhance mental well-being among students of SMK Muhammadiyah Kartasura - Widodo, Arif; Oktaviana, Wita; Azani, Muhammad Zakki; Indahsari, Madya Maya; Nurtiningtyas, Vivi; Febriani, Diana; Agustin, Diva Penni (Universitas Muhammadiyah Magelang, 2025)
The rising prevalence of mental health issues among adolescents, particularly stress and anxiety, necessitates effective interventions within the school environment. This community service program aims to identify and reduce anxiety and stress levels among 325 students at SMK Muhammadiyah Kartasura. The methodology involved initial surveys, in-depth interviews, and coping skills-based interventions. Results indicated that the